Review of Virus Inactivation by Visible Light - Hessling, Martin; Lau, Bernhard; Vatter, Petra (Photonics, 2022)
The COVID-19 pandemic is driving the search for new antiviral techniques. Bacteria and fungi are known to be inactivated not only by ultraviolet radiation but also by visible light. Several studies have recently appeared on this subject, in which viruses were mainly irradiated in media. However, it is an open question to what extent the applied media, and especially their riboflavin concentration, can influence the results. A literature search identified appropriate virus photoinactivation publications and, where possible, viral light susceptibility was quantitatively determined in terms of average log-reduction doses. Sensitivities of enveloped viruses were plotted against assumed riboflavin concentrations. Viruses appear to be sensitive to visible (violet/blue) light. The median log-reduction doses of all virus experiments performed in liquids is 58 J/cm2. For the non-enveloped, enveloped and coronaviruses only, they were 222, 29 and 19 J/cm2, respectively. Data are scarce, but it appears that (among other things) the riboflavin concentration in the medium has an influence on the log-reduction doses. Experiments with DMEM, with its 0.4 mg/L riboflavin, have so far produced results with the greatest viral susceptibilities. It should be critically evaluated whether the currently published virus sensitivities are really only intrinsic properties of the virus, or whether the medium played a significant role. In future experiments, irradiation should be carried out in solutions with the lowest possible riboflavin concentration.